Corneal Biomechanical Properties of Various Types of Glaucoma and Their Impact on Measurement of Intraocular Pressure - Zhang, Yang; Bian, Ailing; Hang, Qijun; Li, Lüe; Zhang, Shunhua; Cheng, Gangwei; Zhou, Qi (Ophthalmic research, 2023)
Abstract Introduction: Corneal biomechanical properties could affect intraocular pressure (IOP) measurement. The aim of this study was to evaluate the differences in corneal biomechanical properties of various types of glaucoma, assess their effect on IOP measurements. Methods: This is an observational clinical study of 486 subjects including 102 normal subjects, 104 ocular hypertension (OHT), 89 normal tension glaucoma (NTG), and 191 high tension glaucoma (HTG). Corneal biomechanical parameters were measured using an ocular response analyzer. The main parameters assessed were corneal hysteresis (CH), corneal resistance factor (CRF), Goldmann-correlated pressure measurement (IOPg), and corneal-compensated intraocular pressure (IOPcc). Ultrasound pachymetry was used to measure central corneal thickness (CCT). IOP was measured by a Goldmann applanation tonometer (GAT) and a noncontact tonometer (NCT). Visual field (VF) and refractive status were also recorded. Results were analyzed by one-way analysis of variance, univariate and multivariate linear regression analyses, and Bland-Altman plots. Results: Multiple comparison by analysis of variance showed significantly lower CH and CRF in NTG compared to HTG, OHT, and normal subjects (CH: 0.011, 0.015, and 0.033; CRF: 0.001, <0.001, and 0.042, respectively). CRF and CH associated with IOP were measured using either GAT, NCT and IOPcc-GAT, IOPcc-NCT, yet CCT was not. GAT correlated strongly with IOPg (r = 0.79; p < 0.001) and IOPcc (r = 0.77; p < 0.001), but limits of agreement between the measurements were poor. CH and CRF were both negatively correlated with VF change (p < 0.01). Conclusion: CH and CRF affect the measurement of IOP and were related to types of glaucoma or severity of glaucoma. Pure CCT should not be used to correct IOP values or estimate the risk of disease.